Efficacy and safety of autologous stem cell transplantation in first-line treatment and at relapse in elderly patients with multiple myeloma - Klein, Eva-Maria; Hujic, Sejla; Miah, Kaya; Benner, Axel; Merz, Maximilian; Bertsch, Uta; Weinhold, Niels; Goldschmidt, Hartmut; Sauer, Sandra (Oncology, 2024)
INTRODUCTION: Although recent data suggest that melphalan high-dose therapy followed by autologous stem cell transplantation (HDT/ASCT) is safe and effective in eligible multiple myeloma (MM) patients up to the age of 75 years, its value in elderly MM patients is still controversially discussed. - METHODS: We retrospectively analyzed 607 MM patients ≥60 years old, who were admitted to our institution for first-line or salvage HDT/ASCT between January 2007 and October 2018. We assigned them to three groups according to age at HDT/ASCT: 60-64 years (S1), 65-69 years (S2) and ≥70 years (S3). We compared progression-free and overall survival, duration of hospitalization, complications, transfers to intermediate or intensive care unit, readmissions after discharge and deaths within 100 days after HDT/ASCT between these groups. - RESULTS: Age did not impact progression-free and overall survival after first-line and salvage HDT/ASCT. Patients ≥70 years old at first HDT/ASCT had a longer hospitalization compared to patients 60-64 years old; however, the difference in the length of hospitalization was only marginal. Rates of febrile neutropenia, mucositis, transfers to intermediate or intensive care unit, readmissions after discharge, and deaths within 100 days after HDT/ASCT were similar in the 3 age groups of patients receiving first or salvage HDT/ASCT. Patients with a Charlson Comorbidity Index ≥2 receiving first HDT/ASCT had a higher risk for a transfer to intermediate or intensive care unit. - CONCLUSION: Our analysis shows that HDT/ASCT is safe and effective in eligible elderly MM patients in first-line treatment and at relapse. A careful patient selection according to biological rather than chronological age is of crucial importance.